Analyzing Materials and Determining their Physical Properties Using Spectral Sensing Technology from Satellite Images: Methodology and Applications - Salman, Salema Sultan; Ismael, Ban S. (Iraqi Journal of Science, 2026)
The spectral remote sensor technology was used to study the Kurdistan region of Iraq to determine the characteristics of surface minerals and by analyzing satellite images across multiple spectral ranges, distinctive spectral signatures were specified for several metals such as zinc (ZN), Lead (PB), and Parium (BA), as well as the use of thermal infrared to detect free abnormalities and the results were verified through field measurements and admonitory, where the selection accuracy was 85% according to the absolute error (MAPE) and 0.045 for RMSé and the results showed that spectral signatures for metals were distributed in nearby and remote IR ranges, helping to determine mineral sediments such as zinc and lead in carbonate rocks and infrared data and it also revealed a surface temperature between 20°C and 35°C, with thermal anomaly indicating metal concentrations and the study confirms the effectiveness of spectral remote sensing as an inexpensive and accurate tool for minerals, which enhances sustainable resource management strategies in Iraq.